Craft and Care: The Maker Movement, Catherine Blake, and the Digital Humanities. Issue 1 (April 2016) - Reed, Ashley
Abstract : This article examines the popular Maker movement, the scholarly discourse of "critical making, " and the work of digital humanists through an analysis of the working relationship between William and Catherine Blake. It begins by examining the contemporary Maker movement, which claims to embrace William Blake as its "patron saint" even as it increasingly insists on the monetization of Makers' creative labor. This pressure toward monetization—in which garage tinkerers become uncompensated R&D departments for large corporations—is accompanied by an emphatic gendering of Makers as male and productive rather than female and reproductive, erasing and effacing the care work that makes Making possible. Given the Maker movement's appropriation of Blake as symbol, it is instructive to examine the collaborative creative processes of William and his wife Catherine, who facilitated Blake's "making" at every stage, both as care worker and as laborer at the press. Recent scholarship on Catherine, however, falls into the same gendered binaries as discussions of the current Maker movement, a failing this essay remedies by proposing a model of Blakean ecology as a method for reimagining the Blakes' lives. The essay concludes by examining Catherine's presence and the role of care work in the William Blake Archive and calling for a critical digital humanities that foregrounds and rewards affective labor.